To market, to market - Miranda, Anne.; Stevens, Janet (San Diego : Harcourt Brace, 1997)
Starting with the nursery rhyme about buying a fat pig at market, this tale goes on to describe a series of unruly animals that run amok, evading capture and preventing the narrator from cooking lunch.
Notable/Best Books (A.L.A.)
School Library Journal
Publisher's Weekly
1.5
K-3
Keywords: Grocery shopping -- Fiction; Stories in rhyme; Shopping -- Fiction; Stories in rhyme